Impact of a fall prevention program in the Internal Medicine wards of a tertiary care university hospital - Lara Medrano, Reynaldo; Alcázar Quiñones, Carlos; Galarza Delgado, Dionicio Ángel; Baena Trejo, Laura (UANL. Facultad de Medicina, 2014)
Objective: To determine whether a falls prevention program reduces the incidence of falls within a hospital. Materials and methods: Each patient admitted to the Internal Medicine ward was classiied into a risk category (high, medium, low) according to the scale of J.H. Downton, and then various general and speciic measures were applied by risk group. Interventions included appointments, teaching materials, and training of medical staff and family. Furthermore, a registration system was developed that allowed adverse event fe edback to the program and identiicat ion of the causes of the fall. The SPSS version 20.0 was used for the data analysis. Descriptive analysis was used for quantitative variables, and qualitative variables were expressed as proportions. To compare the rate of pre- and post-program implementation falls, x 2 was used, with a  = 0.05 determining a signiicant statistical value. Results: Since the implementation of the program, the rate of falls per 1000 days/patient decreased from 1.9 in 2007 to 0.67 in the period 2008-2013, representing a decrease of the rate of falls of up to 70%, with a statistically signiicant difference (P=.02). Conclusions: The implementation of a falls prevention program is an effective tool and reduces the rate and complications associated with them.